2009
DOI: 10.1007/s11258-009-9671-7
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal effectiveness in a plant–lizard interaction and its consequences for plant regeneration after disperser loss

Abstract: Mutualistic disruptions, such as those promoted by the loss of seed dispersers, can have negative effects on the plant regeneration of those species that strongly depend upon them. In order to adequately assess how plant communities are affected by such disruptions, we need to know the importance of the dispersal phase, both in its quantitative and qualitative components. We examined this in the narrow interaction between the shrub Daphne rodriguezii and its (only) disperser, the lizard Podarcis lilfordi. We q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…Once again, regarding the work of Rodríguez-Pérez and Traveset [21], it was observed that seedlings of seeds deposited under the mother plant had lower survival rates compared to the seeds dispersed. Accordingly, even though the passage through the digestive tract of lizards does not significantly increase the germination rate, the deposition pattern of seeds increases the viability of seedlings survival.…”
Section: Lizards As a Seed Dispersermentioning
confidence: 94%
See 4 more Smart Citations
“…Once again, regarding the work of Rodríguez-Pérez and Traveset [21], it was observed that seedlings of seeds deposited under the mother plant had lower survival rates compared to the seeds dispersed. Accordingly, even though the passage through the digestive tract of lizards does not significantly increase the germination rate, the deposition pattern of seeds increases the viability of seedlings survival.…”
Section: Lizards As a Seed Dispersermentioning
confidence: 94%
“…Rodríguez-Pérez and Traveset [21] studied the interaction between Daphne rodriguezii, an endemic shrub from Menorca Island (in Spain), with the lizard Podarcis lilfordi (Günther, 1874), which is its disperser. In such study the seeds size was not an important factor for the selection of fruits, because seeds are not predictors of the amount of pulp mass.…”
Section: Food Preference In Herbivorous and Omnivorous Lizardsmentioning
confidence: 99%
See 3 more Smart Citations